(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): The importance of internal trainings in an organization. Purpose: The purpose of research is to examine and present internal trainings in an organization and their contribution to greater success of an organization. The paper studies employee training in a company, how the organization itself looks after its employees during training, how trainings contribute to further development of organization and the advancement of knowledge for successful operation of organization. Method: How to achieve the purpose of research, used methods and theoretical approach. Results: Specific examples and opinions of employees. Results show the importance of trainings for an organization. We can see that all employees are fairly motivated and ready to participate in trainings and can adapt to changing business environment very well. The results demonstrate that all trainings in the organization are very important and welcome. Only with continuous learning, the organization can be successful and survive in the market despite strong competition. Organization: Trainings are designed for all employees inside an organization. Different employees participate in trainings in a different way as all trainings are divided into certain work and fields that are important for each individual or department in an organization. Society: Trainings have an impact on the whole organization by contributing to its development. Originality: The originality of study is what was new in the research, what is the value and originality of research. Limitations/Future Research: Research was limited to a small number of sources.